2004
DOI: 10.1159/000081198
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Curcumin, Capsaicin and Garlic on the Antioxidant Status of Red Blood Cells and the Liver in High-Fat-Fed Rats

Abstract: Background/Objective: An animal study was carried out to examine the beneficial influence of known hypolipidemic spice principles – curcumin and capsaicin – and the spice garlic on the antioxidant status of red blood cells and liver tissue in hyperlipidemic rats. Methods: Rats were rendered hyperlipidemic by maintaining them on a high-fat (30%) diet for 8 weeks. Spice principles – curcumin (0.2%) or capsaicin (0.015%) – or garlic (2.0%) were included in the diets of separate animal groups. Erythrocytes isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 51 publications
3
56
1
1
Order By: Relevance
“…Additionally, GPX I gene expression was found quite elevated in the capsaicin administered diabetes group compared to the controls. This was attributed both to capsaicin's inhibitory effects on oxidative stress [25] and, partially, free radical formation [40] by augmenting antioxidant molecules and enzymes, and also to its antioxidant actions originating from its phenolic OH groups [41] and its stimulant effect on antioxidant defense system [40] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, GPX I gene expression was found quite elevated in the capsaicin administered diabetes group compared to the controls. This was attributed both to capsaicin's inhibitory effects on oxidative stress [25] and, partially, free radical formation [40] by augmenting antioxidant molecules and enzymes, and also to its antioxidant actions originating from its phenolic OH groups [41] and its stimulant effect on antioxidant defense system [40] .…”
Section: Discussionmentioning
confidence: 99%
“…As a regulatory molecule having certain effects on fat and energy metabolism, capsaicin has also been reported to possess some anti-obesity properties by lowering the blood fat content and inhibiting proliferation of the white fat cells [24] . Furthermore, it has been suggested that capsaicin has oxidative stress lowering effects by increasing the levels of antioxidant molecules and enzymes especially in liver and erythrocytes [25] .…”
Section: Introductionmentioning
confidence: 99%
“…22 Mechanism of action of curcumin and capsaicin on health beneficial activity have been extensively studied and reported. 23,24,25 Although these two spice principles share a considerable amount of structural homology nevertheless possesses notable differences in the mechanism of action. The present study was designed to evaluate protective effect of combined curcumin and capsaicin against LPS-induced inflammation in mice.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Dietary curcumin, capsaicin and garlic were protective against oxidative damage to erythrocytes and liver of hyperlipidemic/hypercholesterolemic rats. 21,22 Curcumin and capsaicin are protective to iron induced hepatotoxicity, where deposition of iron in hepatic parenchymal cells results in fibrosis and cirrhosis which was measured in terms of lipid peroxidation and elevated levels of plasma alanine aminotransferase, aspartate aminotransferase and lactate dehydrogenase. These beneficial effects were found to be more when the two compounds were fed in combination.…”
Section: Introductionmentioning
confidence: 99%